The Impact of Pancreatic Exocrine Diseases on the β-Cell and Glucose Metabolism—A Review with Currently Available Evidence - Marina Ciochina; Daniel Vasile Balaban; George Manucu; Mariana Jinga; Cristian Gheorghe (Biomolecules, 2022)
Pancreatic exocrine and endocrine dysfunctions often come together in the course of pancreatic diseases as interdependent manifestations of the same organ. However, the mechanisms underlying the bidirectional connection of the exocrine and endocrine pancreas are not fully understood. In this review, we aimed to synthetize the current knowledge regarding the effects of several exocrine pancreatic pathologies on the homeostasis of β-cells, with a special interest in the predisposition toward diabetes mellitus (DM). We focused on the following pancreatic exocrine diseases: chronic pancreatitis, acute pancreatitis, cystic fibrosis, pancreatic cancer, pancreatic resections, and autoimmune pancreatitis. We discuss the pathophysiologic mechanisms behind the impact on β-cell function and evolution into DM, as well as the associated risk factors in progression to DM, and we describe the most relevant and statistically significant findings in the literature. An early and correct diagnosis of DM in the setting of pancreatic exocrine disorders is of paramount importance for anticipating the disease’s course and its therapeutical needs.